2002
DOI: 10.1088/0953-8984/14/6/104
|View full text |Cite
|
Sign up to set email alerts
|

A muon-spin relaxation (µSR) study of the geometrically frustrated magnets Gd3Ga5O12and ZnCr2O4

Abstract: We present the results of muon-spin-relaxation experiments for two materials which show geometric frustration. ZnCr 2 O 4 has a spinel structure with S = 3 2 spins on a lattice of corner-sharing tetrahedra. Our experiments show that a local magnetic field which is quasi-static on the muon timescale develops below T c = 12.5 K, a transition which has been associated with a three-dimensional analogue of the spin-Peierls transition. In contrast, Gd 3 Ga 5 O 12 has a garnet structure with S = 7 2 spins arranged on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 25 publications
4
36
0
Order By: Relevance
“…We note that a linear variation has also been encountered theoretically for the case of a frustrated Heisenberg pyrochlore antiferromagnet [5]. The decrease in the relaxation rate followed by a saturation is similar to the behaviour observed (by µSR [13]) in the isomorphous compound Gd 3 Ga 5 O 12 .…”
Section: B Quantitative Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…We note that a linear variation has also been encountered theoretically for the case of a frustrated Heisenberg pyrochlore antiferromagnet [5]. The decrease in the relaxation rate followed by a saturation is similar to the behaviour observed (by µSR [13]) in the isomorphous compound Gd 3 Ga 5 O 12 .…”
Section: B Quantitative Analysissupporting
confidence: 80%
“…A number of the rare earth garnets appear to evidence a conventional long range ordered state [7] suggesting that in these cases, frustration plays a negligible role. In fact, to date, frustration has been reported to play a major role in only one garnet, Gd 3 Ga 5 O 12 [8][9][10][11][12][13], where the S-state Gd 3+ ion has a very small intrinsic anisotropy and where the dominant coupling is antiferromagnetic.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, residual low temperature dynamics has been found in pyrochlore magnetic materials with low temperature states that range from not understood whatsoever 21,29 to seemingly conventional long range ordered 16,17,18,19,20 . We note in passing that persistent low-temperature spin dynamics has also been found in the Gd 3 Ga 5 O 12 garnet (GGG) 30,31 and in the SrCr 8 Ga 4 O 19 kagome antiferromagnet 32 . We now briefly review the various experimentally observed behaviors of the R 2 Ti 2 O 7 and R 2 Sn 2 O 7 pyrochlore oxides.…”
Section: Introduction a Persistent Spin Dynamics In Pyrochloresmentioning
confidence: 63%
“…In GGG, a spin-liquid state is observed at temperatures above a spin-glass transition at T g ≈ 0.14 K (13). Evidence for a conventional spin liquid in GGG is the suppression of T g to temperatures far below the antiferromagnetic interaction strength of ∼2 K (14-16), the observation of liquid-like magnetic diffuse scattering in powder neutron-scattering measurements (17), and the persistence of strong spin fluctuations to low temperature (18)(19)(20). Yet, broad anomalies are present in both the non-linear susceptibility χ 3 and the magnetic specific heat at around 0.5 K, which do not yet have a well-understood microscopic origin (13,21).…”
mentioning
confidence: 99%